The stress of combat the combat of stress : caring strategies towards ex-service men and women - Roy, Brook (The Alpha Press, 1999)
Roy Brook's job was to locate and assess war veterans experiencing difficult personal circumstances to make sure that they were receiving full entitlement to a War Disability Pension, and other benefits, and grants of money and proper care. This book tells the story of the horrors and fears these veterans could not leave behind on the battlefield, and which continue to haunt them and disrupt their lives, and those close to them." "This book is an essential guide to a wide range of battle stress, war-experience and mental conditions. The case histories and types of patients will be of interest to the Caring Professions, the Social services, the Armed Forces, and to all Families with members serving, or who have served, in the Armed Forces.